2022
DOI: 10.1002/ajpa.24666
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic history of mitochondrial haplogroup J in Scandinavia

Abstract: Background: Mitochondrial DNA haplogroup J is the third most frequent haplogroup in modern-day Scandinavia, although it did not originate there. To infer the genetic history of haplogroup J in Scandinavia, we examined worldwide mitogenome sequences using a maximum-likelihood phylogenetic approach.Methods: Haplogroup J mitogenome sequences were gathered from GenBank (n = 2245) and aligned against the ancestral Reconstructed Sapiens Reference Sequence. We also analyzed haplogroup J Viking Age sequences from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
1
0
0
Order By: Relevance
“…Haplogroup J is believed to have originated approximately 45,000 years ago, likely in West Asia, specifically the Near East or Caucasus regions. Interestingly, recent research by Kristjansson et al revealed that mitochondrial DNA haplogroup J is also the third most frequent haplogroup in modern-day Scandinavia, despite not originating there [24]. Within our study, the majority of haplogroup J1 was represented by J1a (frequency of 11.24%), with J1b (including J1b1b1) being the more prevalent subclade at a frequency of 7.52%.…”
Section: Results and Discussion: Mt-dna Haplogroup Frequencysupporting
confidence: 52%
“…Haplogroup J is believed to have originated approximately 45,000 years ago, likely in West Asia, specifically the Near East or Caucasus regions. Interestingly, recent research by Kristjansson et al revealed that mitochondrial DNA haplogroup J is also the third most frequent haplogroup in modern-day Scandinavia, despite not originating there [24]. Within our study, the majority of haplogroup J1 was represented by J1a (frequency of 11.24%), with J1b (including J1b1b1) being the more prevalent subclade at a frequency of 7.52%.…”
Section: Results and Discussion: Mt-dna Haplogroup Frequencysupporting
confidence: 52%